Effect of a mental health education intervention on children’s life satisfaction and self-confidence in rural China - Long, Zhengyu; Wang, Ke; Wang, Hui; Yao, Weiwei; Liu, Chunrong (Frontiers in Psychology, 2023)
Children living in rural areas may potentially experience low levels of life satisfaction and face challenges in developing self-confidence. The purpose of the current study was to examine the impact of a mental health education intervention on the life satisfaction and self-confidence of children residing in rural areas of China. A total of 1,001 children from grades 4 to 6 were randomly assigned to an intervention group (475 children, 250 boys, M = 11.57 years, SD = 1.082 years) and a control group (526 children, 279 boys, M = 11.38 years, SD = 0.980 years). Over 16 weeks, the intervention group received a mental health education program, while the control group did not. The levels of life satisfaction (including five dimensions: family, school, environmental, friends, and self-satisfaction) and self-confidence (including three dimensions: self-efficacy, self-assurance, and self-competence) were rated by all children at baseline and post-intervention. Results from paired samples t-test showed that post-intervention, the intervention group exhibited significant improvements in the areas of family, environmental, school, and self-satisfaction as well as self-efficacy, self-assurance, and self-competence. However, there was no significant improvement in friend satisfaction. Conversely, the control group showed decreases in school, environmental, and friend satisfaction, along with decreases in self-efficacy, self-assurance, and self-competence. No significant change was observed in family and self-satisfaction in this group. These findings emphasize the importance of implementing mental health education interventions for rural children, who are at risk for low life satisfaction and self-confidence. Some specific recommendations are provided for policymakers and practitioners.